2018
DOI: 10.1029/2018gl079966
|View full text |Cite
|
Sign up to set email alerts
|

Annual Cycle of Turbulent Dissipation Estimated from Seagliders

Abstract: The rate of dissipation of turbulent kinetic energy is estimated using Seaglider observations of vertical water velocity in the midlatitude North Atlantic. This estimate is based on the large-eddy method, allowing the use of measurements of turbulent energy at large scales O(1-10 m) to diagnose the rate of energy dissipated through viscous processes at scales O(1 mm). The Seaglider data considered here were obtained in a region of high stratification (1 × 10 −4 < N < 1 × 10 −2 s −1 ), where previous implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…The OSMOSIS site lies at the eastern edge of the North Atlantic subtropical gyre, a region of weak mean flow and moderate eddy kinetic energy that is arguably representative of a substantial fraction of the global ocean. While one-dimensional turbulent processes associated with air-sea buoyancy and wind forcing are found to be the dominant driver of upper-ocean turbulent dissipation over an annual cycle (Evans et al, 2018), our case study demonstrates that SI can play an important role in sustaining dissipation at depths beyond the influence of surface waves. Further, our work suggests that SI may be a common feature throughout the quiescent regions of the ocean, where it can be induced by the occasional alignment of surface winds with transient upper-ocean fronts generated by mesoscale frontogenesis.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The OSMOSIS site lies at the eastern edge of the North Atlantic subtropical gyre, a region of weak mean flow and moderate eddy kinetic energy that is arguably representative of a substantial fraction of the global ocean. While one-dimensional turbulent processes associated with air-sea buoyancy and wind forcing are found to be the dominant driver of upper-ocean turbulent dissipation over an annual cycle (Evans et al, 2018), our case study demonstrates that SI can play an important role in sustaining dissipation at depths beyond the influence of surface waves. Further, our work suggests that SI may be a common feature throughout the quiescent regions of the ocean, where it can be induced by the occasional alignment of surface winds with transient upper-ocean fronts generated by mesoscale frontogenesis.…”
Section: Discussionmentioning
confidence: 66%
“…The rate of dissipation of turbulent kinetic energy ϵ obs is estimated from high-frequency fluctuations in the glider vertical velocity using a generalization of the large eddy method of Beaird et al (2012) developed by Evans et al (2018) and used here to explore the key contributions to dissipation at the transient front. A filter with a cutoff dependent on the local buoyancy frequency is applied to glider vertical velocity estimates to remove internal wave variability.…”
Section: Calculation Of Turbulent Dissipation Ratementioning
confidence: 99%
“…In this paper, we present results from a 4-month glider mission that sampled an anticyclonic mesoscale eddy located at the western boundary of the North Atlantic subtropical gyre, at 268N west of the Great Abaco Island (Bahamas). The observed variability of turbulent kinetic energy (TKE) dissipation rates within the eddy, inferred from glider-derived vertical seawater velocities using a large-eddy approximation (Beaird et al 2012;Evans et al 2018), was found to be consistent with the breaking of internal waves due to eddy-wave interactions. After describing the data collection procedures and methodologies (section 2), we present the general hydrographic conditions and the characteristics of the anticyclonic eddy, as well as the distribution of TKE dissipation, in section 3.…”
Section: Introductionmentioning
confidence: 75%
“…Additionally, there is the implicit assumption of no energy leakage such that, in a stationary state, the rates of energy transfer and dissipation are equivalent (Gargett 1999). The LEM was first applied to glider data by Beaird et al (2012) to study the variability of turbulent dissipation associated with the Nordic Sea inflows, and later by Evans et al (2018) to investigate the seasonal variability of near surface mixing in the North Atlantic at 488N. In both cases, glider-derived « compared favorably with independent direct estimates from microstructure shear and acoustic Doppler current profiler (ADCP) velocity measurements, and indirectly with boundary layer scalings.…”
Section: B Turbulent Kinetic Energy Dissipation Inferred From the Sementioning
confidence: 99%
“…The pioneering work of Moum et al (2013), who created a 6-yr record of turbulence estimates from high-frequency temperature measurements in the equatorial Pacific, found a seasonal cycle in turbulence that was responsible for cooling sea surface temperature. Glider based measurements find that upper ocean turbulence is modulated by wind and buoyancy forcing (Evans et al 2018). Moored profiler based estimates of turbulent overturns on the Mid-Atlantic Ridge find a correlation between overturn size and the phase of the tide (Clément et al 2017).…”
Section: Introductionmentioning
confidence: 99%